La perífrasis ir a + infinitivo y la expresión de la posterioridad en el habla culta de Costa Rica - Pitloun, Petr (2004)
The purpose of this investigation is to describe the use of the periphrastic construction ir a + infinitive in cultivated Spanish of Costa Rica. Furthermore, the study aims to find out the position this construction occupies among the forms that are used to indicate future events with reference both to the speech point and to a time point anterior to the act of speech. 11 is a descriptive study based on the material collected within the framework of the Project of Coordinated Study of the Standard Linguistic Norm of the Principal Cities of Latin America and Spain. Findings are that the periphrastic construction ir a + infinitive is used mostly (in 64,7% of all documented cases) with the auxiliary verb in present indicative to express future events with reference to the speech point. In general, the temporal use of this construction prevails significantly over its non-temporal use. Results also indicate that it is the most frequent form among the forms used to indicate future events referred both lo the speecb moment and to some past time point.